Pengaruh Konflik Komunikasi Petugas Aviation Security (AVSEC) terhadap Penumpang Ditinjau dari Komunikasi Interpersonal di Bandar Udara Sultan Thaha Jambi - Fiqri Yansyah Icshan; Kartika Fajar Nieamah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Interpersonal communication is a communication process between two or more people face-to-face that allows the communicator to convey messages directly and the communicant to respond to them at the same time. This process helps us understand the meaning of messages in communication, even when they are silent, they can be said to be communicating. Interpersonal communication becomes very important in the continuity and smoothness of work, as done by aviation security (AVSEC) officers at Sultan Thaha Airport Jambi. The purpose of this study is to determine the effect of aviation security (AVSEC) communication conflicts on passengers in terms of interpersonal communication at Sultan Thaha Airport Jambi. This research uses quantitative methods. Data collection techniques by distributing questionnaires to 100 respondents. The research instrument used a Likert scale with 23 statements according to the indicators of each variable. This research uses SPSS for instrument testing and hypothesis testing, namely simple linear regression analysis. The results of this study indicate that there is an influence between the independent variable, namely interpersonal communication, on the dependent variable, namely communication conflicts that have a significant effect with the data obtained 0.010 < 0.05 with the value of tcount > ttable, which is 2.612 > 1.660. This can be seen in the research hypothesis which shows that Ha is accepted and H0 is rejected. The magnitude of the influence of the interpersonal communication variable can be seen from the results of the coefficient of determination (R2) test of 0.065. This shows that there is an influence of the interpersonal communication variable (X) on the communication conflict variable (Y) of 6.5%.